Custom affinity probes reveal DNA-damage-induced, ssDNA-independent chromatin SUMOylation in budding yeast - Vera Tröster; Ronald P. Wong; Arne Börgel; Baris Cakilkaya; Christian Renz; Martin M. Möckel; Karolin Eifler-Olivi; Joana Marinho; Thomas Reinberg; Sven Furler; Jonas V. Schaefer; Andreas Plückthun; et al. (Cell Reports)
Summary: The small ubiquitin-related modifier SUMO regulates cellular processes in eukaryotes either by modulating individual protein-protein interactions or with relaxed substrate selectivity by group modification. Here, we report the isolation and characterization of designed ankyrin repeat protein (DARPin)-based affinity probes directed against budding yeast SUMO (Smt3). We validate selected DARPins as compartment-specific inhibitors or neutral detection agents. Structural characterization reveals a recognition mode distinct from that of natural SUMO interactors. In vivo application pinpoints Smt3’s essential function to the nucleus and demonstrates DARPin-mediated sensitization toward various stress conditions. A subset of selected clones is validated as SUMOylation reporters in cells. In this manner, we identify a DNA-damage-induced nuclear SUMOylation response that—in contrast to previously reported chromatin group SUMOylation—is independent of single-stranded DNA and the SUMO-E3 Siz2 but depends on Mms21 and likely reflects late intermediates of homologous recombination. Thus, Smt3-specific DARPins can provide insight into the dynamics of SUMOylation in defined subcellular structures.